ENERGY AND AVERAGES IN THE MECHANICS OF GRANULAR MATERIALS - Muhlhaus H.B.; Hornby P. (My University, 2001)
We derive a general thermo-mechanical theory for particulate materials consisting of granules of arbitrary whose material points possess three translational and three independent rotational degrees of freedom. Additional field variables are the translational and rotational granular temperatures, the kinetic energies shape and size. The kinematics of granulate is described within the framework of a polar continuum theory of the velocity and spin fluctuations respectively and the usual thermodynamic temperature. We distinguish between averages over particle categories (averages in mass/velocity and moment of inertia/spin space, respectively) and particle phases where the average extends over distinct subsets of particle categories (multi phase flows). The relationship between the thermal energy in the granular system and phonon energy in a molecular system is briefly discussed in the main body of the paper and discussed in detail in the Appendix A.
Keywords: GRANULAR MATERIALS; THERMO-MECHANICAL THEORY; MULTI PHASE FLOWS